2010
DOI: 10.3390/md8092466
|View full text |Cite
|
Sign up to set email alerts
|

Marine Myxobacteria as a Source of Antibiotics—Comparison of Physiology, Polyketide-Type Genes and Antibiotic Production of Three New Isolates of Enhygromyxa salina

Abstract: Three myxobacterial strains, designated SWB004, SWB005 and SWB006, were obtained from beach sand samples from the Pacific Ocean and the North Sea. The strains were cultivated in salt water containing media and subjected to studies to determine their taxonomic status, the presence of genes for the biosynthesis of polyketides and antibiotic production. 16S rDNA sequence analysis revealed the type strain Enhygromyxa salina SHK-1T as their closest homolog, displaying between 98% (SWB005) and 99% (SWB004 and SWB006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…1). The predominance of SCFAs in both genera (19,20) (20,43), but here, a predominance of straight-chain C 16:17c (42%), C 18:19c (29%), and C 16:0 (11%) was found. Although this study reproduced these findings with regard to detection of these FAs, the absence of quantitative data in previous studies prevents a true comparison.…”
Section: Resultsmentioning
confidence: 93%
“…1). The predominance of SCFAs in both genera (19,20) (20,43), but here, a predominance of straight-chain C 16:17c (42%), C 18:19c (29%), and C 16:0 (11%) was found. Although this study reproduced these findings with regard to detection of these FAs, the absence of quantitative data in previous studies prevents a true comparison.…”
Section: Resultsmentioning
confidence: 93%
“…The addition of sodium [1,[2][3][4][5][6][7][8][9][10][11][12][13] C2]acetate to the culture medium of H. ochraceum led to the enhancement of 13 C-NMR signals of C-4 (δC 126.8, d, J = 56 Hz), C-5 (δC 125.5, d, J = 56 Hz) and C-10 (δC 112.4, s), corresponding one intact acetate unit and one acetate-derived terminal methylene in the haliamide structure ( Figure 3). The second feeding experiment with sodium [1-13 C]propionate gave two isotope-labeled carbons of C-7 (δC 47.4) and C-9 (δC 144.2).…”
Section: Identification Of the Biosynthetic Precursorsmentioning
confidence: 99%
“…Although long been regarded as terrestrial microorganisms, several halophilic myxobacterial strains have been noticed recently [4][5][6][7][8] and found to be excellent producers of novel secondary metabolites, such as polyketides (PKs), non-ribosomal peptides (NRPs) and their hybrids. A recent report suggested that the polyketide synthase (PKS) gene sequences in marine-derived myxobacterial isolates are highly novel (all of the sequences were less than 70% similar to the known ones) [9].…”
Section: Introductionmentioning
confidence: 99%
“…They predominantly inhabit terrestrial but their presence is also reported in aquatic environment and they have been isolated from tree bark and animal dung. The genomes of the Myxobacteria have high GC content of ~70% [13,14]. Myxobacteria have unique characteristics among the bacteria as they show coordinated motility, predation and produce multicellular fruiting bodies under nutrient limited condition [15].…”
Section: Introductionmentioning
confidence: 99%